The perfect wizard : Hans Christian Andersen - Yolen, Jane.; Nolan, Dennis, 1945- (New York : Dutton's Children's Books, 2004)
A biography of the famous Danish writer of fairy tales, interspersed with excerpts from his stories.
Includes bibliographical references.
Wilson's Children.
School Library Journal.
Book Links (A.L.A.).
4.3
K-3
Keywords: Andersen, H. C., -- 1805-1875 -- Juvenile literature; Andersen, H. C., -- 1805-1875.; Andersen, H. C., -- 1805-1875.; Authors, Danish -- 19th century -- Biography -- Juvenile literature; Authors, Danish; Danish authors -- Biography; Authors, Danish